A positive association of serum CCN5/WISP2 levels with the risk of developing gestational diabetes mellitus: a case–control study - Mohammed Farhan Hamdan Alshganbee; Fariba Nabatchian; Vida Farrokhi; Reza Fadaei; Nariman Moradi; Reza Afrisham (Journal of Physiological Sciences)
Abstract Introduction CCN5/WISP2 is prominently manifest in adipose tissue and has been linked to the pathogenesis of obesity, diabetes, and insulin resistance. However, discrepancies exist in previous studies, and little is known about its association with gestational diabetes mellitus (GDM). The current investigation is designed to examine the correlation of WISP2 with risk factors in GDM patients in comparison to healthy pregnant women for the first time. Methods This case–control study measured serum levels of CCN5, TNF-α, IL-6, adiponectin, and fasting insulin using ELISA kits in 88 GDM patients and 88 pregnant women. Results The GDM group had remarkably higher serum levels of CCN5 (379.41 ± 83.078 ng/ml) compared to controls (212.02 ± 77.935 ng/ml). In a similar vein, it was observed that patients diagnosed with GDM exhibited elevated levels of pro-inflammatory cytokines such as IL-6 and TNF-α; while conversely, adiponectin levels were found to be significantly lower than those observed in the control group (P < 0.0001). In women with GDM, a positive and significant correlation was observed between CCN5 and BMI, FBG, insulin, HOMA-IR, as well as IL-6 and TNF-α levels. In the adjusted model, the risk of GDM was significantly increased with elevated serum CCN5 level. Conclusion Our research indicates a noteworthy and affirmative correlation between the levels of CCN5 in the serum and the risk of developing GDM, along with its associated risk factors such as BMI, insulin resistance index, FBG, and inflammatory cytokines (TNF-α and IL-6). These findings suggest that CCN5 could potentially play a role in the etiology of GDM.